2021
DOI: 10.1111/rec.13547
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of herb‐layer vegetation and soil properties after pile burning in a Midwestern oak woodland

Abstract: Thinning and removal of woody vegetation is the first step in restoring ecosystem structure to systems altered by woody encroachment. However, pile burning—a common method of eliminating woody residue at restoration sites—can promote the establishment of exotic species and adversely impact soils and native vegetation via extreme soil heating. Despite its widespread use, pile burning effects remain poorly understood in oak woodlands compared to coniferous forests. We examined how pile burning influenced soil pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…To assess soil chemical and physical properties, we randomly collected 10 soil cores (15‐cm depth) in each of the 12 blocks ( n = 40 soil cores per restoration site) (120 soil cores/block), and quantified 14 chemical and physical soil properties using methods outlined in Albrecht et al. (2022) (also see Table S2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess soil chemical and physical properties, we randomly collected 10 soil cores (15‐cm depth) in each of the 12 blocks ( n = 40 soil cores per restoration site) (120 soil cores/block), and quantified 14 chemical and physical soil properties using methods outlined in Albrecht et al. (2022) (also see Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in four 1-m 2 quadrats in each block (n = 16 subplots per restoration site), we recorded percent cover of all herbaceous and woody species (<1.5 m tall) (Full list of vegetative density available in Table S1). To assess soil chemical and physical properties, we randomly collected 10 soil cores (15-cm depth) in each of the 12 blocks (n = 40 soil cores per restoration site) (120 soil cores/block), and quantified 14 chemical and physical soil properties using methods outlined in Albrecht et al (2022) (also see Table S2).…”
Section: Study Site Characterization and Soil Collectionmentioning
confidence: 99%
“…Canopy thinning occurred during winter 2016–2017 on frozen or near‐frozen soils, and focused on larger‐diameter (>10 cm DBH) non‐oak tree species, except in riparian areas (Figure S1). Most woody biomass was piled and burned on site (Albrecht et al, 2022). Prescribed burns were conducted in December 2016 and in November 2017, on days when temperatures ranged from 45 to 55°F, relative humidity from 27% to 45% and maximum wind speeds from 7 to 30 mph.…”
Section: Methodsmentioning
confidence: 99%
“…The reserve lies in the Eastern Ozark Border ecoregion and is approximately 10 km 2 of upland oak‐hickory woodlands, grasslands, wetlands and bottomland forests in varying stages of restoration and management (Reid et al, 2020). The majority of the 27 ha WW management unit consists of upland woodlands on gently sloping terrain (<15%) with east‐ or south‐facing aspect, and moderately drained and slightly acidic to neutral silt‐loam soils (pH: 6.3–7.1; Albrecht et al, 2022). A riparian zone covers a smaller portion of SNR, and consists of typical mesic or floodplain tree species.…”
Section: Methodsmentioning
confidence: 99%
“…Invasive species commonly flourish in unusual habitats rich in resources, and thus, they have high biodiversity and wide distribution. Their extraordinary multitude of species, from aquatic weeds (e.g., Eichhornia crassipes, Pistia stratiotes) to grasses, small (e.g., Poe annua, Cynodon dactylon) and large (e.g., Phragmites australis, Sorghum halepense), forbs and herbs (e.g., Lythrum salicaria, Centaurea solstitialis), vines (e.g., Celastrus orbiculatus, Rosa multiflora), shrubs (e.g., Mimosa pigra, Lantana camara) and trees (e.g., Pinus ponderosa, Castilla elastic) (Albrecht et al 2021). Mallick et al (2019) reported that there were 132 genera in 165 taxa of invasive plants in the City of Odisha, India.…”
Section: Classification and Habitat Distribution Of Invasive Plantsmentioning
confidence: 99%